2016
DOI: 10.1063/1.4958330
|View full text |Cite
|
Sign up to set email alerts
|

Towards strong light-matter coupling at the single-resonator level with sub-wavelength mid-infrared nano-antennas

Abstract: We report a crucial step towards single-object cavity electrodynamics in the mid-infrared spectral range using resonators that borrow functionalities from antennas. Room-temperature strong light-matter coupling is demonstrated in the mid-infrared between an intersubband transition and an extremely reduced number of sub-wavelength resonators. By exploiting 3D plasmonic nano-antennas featuring an out-of-plane geometry, we observed strong light-matter coupling in a very low number of resonators: only 16, more tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…30 and 2Ω R /ω = 0.05 in Ref. 31). We use the dependence of the polariton splitting on the effective mode volume as a near field probe to estimate the highly subwavelength volume of our resonators in comparison with reference microcavity systems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…30 and 2Ω R /ω = 0.05 in Ref. 31). We use the dependence of the polariton splitting on the effective mode volume as a near field probe to estimate the highly subwavelength volume of our resonators in comparison with reference microcavity systems.…”
mentioning
confidence: 99%
“…We can see that the intersubband plasmon frequencies obtained in the two cases strongly differ from our measurement, confirming the analysis presented above. 29,31,32 In order to improve further the strength of the light-matter coupling, we designed a second sample with an identical absorbing region, but with an increased thickness of the cavity (320 nm) and and increased doping density in the outermost GaAs layers (6 × 10 18 cm −3 ). After processing into patch cavities and LC metamaterials, we perform the same experiments as described above (see Supplementary materials for details).…”
mentioning
confidence: 99%
“…Attempts have been made to reach the single-antenna regime by gradually reducing the total number of array elements, and by increasing the separation between antennae in the array [4,5]. However, neither of these approaches reached the single nanoantenna regime, because the signal became too weak to be detected.…”
Section: Nano-antennas For Investigations Of Isb Polaritonsmentioning
confidence: 99%
“…As appropriate nanofabrication methods become more and more available, different fields have started to benefit from the miniaturization of nanopillars: ongoing research has demonstrated the great potential of nanopillars in photonic crystal structures for the control of a broad range light propagation in broad range of novel optoelectronic devices. Replacing micropillars with nanopillars has proven extremely beneficial also in fields such as nanotechnology, bioelectronics, and biosensors, where devices are being made with increasingly smaller features .…”
Section: Introductionmentioning
confidence: 99%